Differentiation of the SH-SY5Y Human Neuroblastoma Cell Line - Shipley, Mackenzie M.; Mangold, Colleen A.; Szpara, Moriah L. (Journal of visualized experiments, 2016)
Having appropriate in vivo and in vitro systems that provide translational models for human disease is an integral aspect of research in neurobiology and the neurosciences. Traditional in vitro experimental models used in neurobiology include primary neuronal cultures from rats and mice, neuroblastoma cell lines including rat B35 and mouse Neuro-2A cells, rat PC12 cells, and short-term slice cultures. While many researchers rely on these models, they lack a human component and observed experimental effects could be exclusive to the respective species and may not occur identically in humans. Additionally, although these cells are neurons, they may have unstable karyotypes, making their use problematic for studies of gene expression and reproducible studies of cell signaling. It is therefore important to develop more consistent models of human neurological disease. The following procedure describes an easy-to-follow, reproducible method to obtain homogenous and viable human neuronal cultures, by differentiating the chromosomally stable human neuroblastoma cell line, SH-SY5Y. This method integrates several previously described methods(1-4) and is based on sequential removal of serum from media. The timeline includes gradual serum-starvation, with introduction of extracellular matrix proteins and neurotrophic factors. This allows neurons to differentiate, while epithelial cells are selected against, resulting in a homogeneous neuronal culture. Representative results demonstrate the successful differentiation of SH-SY5Y neuroblastoma cells from an initial epithelial-like cell phenotype into a more expansive and branched neuronal phenotype. This protocol offers a reliable way to generate homogeneous populations of neuronal cultures that can be used for subsequent biochemical and molecular analyses, which provides researchers with a more accurate translational model of human infection and disease.